Impact of Supplement of Lactobacillus casei K17 on Fillet Tastes of Largemouth Bass Micropterus salmoides - Jinsong WANG; Changzhuo ZHANG; Yan CHEN; Zhuoying ZHU; Huiyu FU; Lanming CHEN (Shipin gongye ke-ji, 2022)
Impact of supplement ofLactobacillus casei K17 on fillet tastes of largemouth bass Micropterus salmoides were researched for improving its fillet tastes. The M. salmoides was given commercial feed supplemented with live L. casei K17 (1×108 CFU/g), live L. casei K17 protected by skim milk powder (10%), heat-killed dead L. casei K17, its fermentation supernatant, skim milk powder (10%), and saline (0.85% NaCl), designated as LB, MB, DB, FS, MG, and SG, respectively. At the end of the trial, the outline of the whole taste difference of each group was determined by using the electronic tongue. The contents of free amino acids and flavor nucleotides were analyzed. The results showed that the electronic tongue adopted discriminant factor analysis based on principal component analysis, the difference of six groups could be effectively distinguished, and the umami, bitter and sweet taste of each group could be effectively distinguished by using radar map. Sixteen free amino acids were detected from the fillet of six groups. Total umami amino acids and aspartic acid (Asp) in the MB group, the valine (Val), isoleucine (Ile), leucine (Leu), phenylalanine (Phe) and total bitter amino acids in the FS group, and the total essential amino acids in the MG group were significantly higher than those in the control SG group (P<0.05). Combined with equivalent umami concentrations (EUC), MB group had the most significant increase in EUC compared with the control group, and the order was MB>FS>DB>LB>MG>SG. Consistent with the predicted results of the electronic tongue, EUC was recommended to quantify the umami of fish fillet. These results showed the fillet taste compositions and contents of M. salmoides fed with different L. casei K17 diets were improved obviously compared with the control group, especially LB and MB, which could provide a useful theoretical reference for further development and utilization of M. salmoides.